2021
DOI: 10.1038/s41419-021-03941-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation mediated RSPO2 to promote follicular development in mammals

Abstract: In female mammals, the proliferation, apoptosis, and estradiol-17β (E2) secretion of granulosa cells (GCs) have come to decide the fate of follicles. DNA methylation and RSPO2 gene of Wnt signaling pathway have been reported to involve in the survival of GCs and follicular development. However, the molecular mechanisms for how DNA methylation regulates the expression of RSPO2 and participates in the follicular development are not clear. In this study, we found that the mRNA and protein levels of RSPO2 signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…The normal development of GCs is necessary to ensure a normal follicular cycle and maintaining the balance between the proliferation and apoptosis of GCs is vitally important for oocyte maturation and embryonic development (39). When this balance is disturbed, follicular development will be either retarded or even terminated (40). It is generally considered that in vitro cell models are particularly valuable for studying steroidogenesis and folliculogenesis, especially for humans and large ruminants (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The normal development of GCs is necessary to ensure a normal follicular cycle and maintaining the balance between the proliferation and apoptosis of GCs is vitally important for oocyte maturation and embryonic development (39). When this balance is disturbed, follicular development will be either retarded or even terminated (40). It is generally considered that in vitro cell models are particularly valuable for studying steroidogenesis and folliculogenesis, especially for humans and large ruminants (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we further revealed a regulatory relationship between these factors in sow GCs and constructed a small regulatory network for controlling GC apoptosis and follicular atresia, with these factors as hub genes. This is different from previous studies on the regulatory mechanism of sow follicular atresia and GC apoptosis, which mainly focused on a single factor [ 45 , 46 ], regulatory axis [ 47 ], or signaling pathway [ 48 , 49 ]. Our findings define, for the first time, a small regulatory network that affects follicular atresia and GC apoptosis in sows, providing a new perspective for revealing the mechanism of complex processes such as GC apoptosis and follicular atresia.…”
Section: Discussionmentioning
confidence: 65%
“…[ 29 , 30 ] CCND1 regulates cyclinD1 protein and promotes cytoplasmic proliferation, Cyclin D1 and its inhibitors are associated with GC proliferation at specific follicular stages, CCND1 promoted E2 secretion of PCOS ovarian GC, increased the expression level of CYP19A1, inhibited the expression level of Caspase 3 in apoptotic GC, and reduced CASP3 cleavage. [ 31 , 32 ] CASP3 is a regulatory factor of apoptosis signaling pathway, the early ovarian stage of PCOS patients is characterized by increased number of follicles, and the apoptosis rate of sinus follicles is related to increased expression of CASP3 in GC. Hyperandrogenemia in the late stage is closely related to excessive GC apoptosis.…”
Section: Discussionmentioning
confidence: 99%